Psilocybin-induced takotsubo cardiomyopathy. Issue 5 (17th May 2022) - Kotts, Wiktoria Julia; Gamble, David T; Dawson, Dana K; Connor, David
Abstract : We present a case of takotsubo cardiomyopathy following recreational ingestion of Psilocybe semilanceata (known as 'magic mushrooms'). The patient presented with respiratory distress and pulmonary oedema responding to standard medical measures. Investigations included: echocardiogram, cardiac MRI and angiogram. Based on our search, we suggest this is only the second recognised case in the published literature.